Neuroendocrine control of calcium mobilization in the fruit fly. - Okamoto, N.; Mizuno, Y.; Watanabe, A.; Kohsaka, H.; Niwa, R. (Nature, 2026)
Calcium (Ca[2+]) is an essential mineral that must be strictly regulated to support numerous physiological activities[1,2]. Extracellular fluid Ca[2+] is regulated in vertebrates through endocrine systems that manage the vast Ca[2+] reservoir in the bones[3-6], but the Ca[2+] regulatory mechanisms used by invertebrates, which lack bones, remain largely unclear. Here we identified a potent peptide hormone, Capa, which is responsible for regulating extracellular fluid Ca[2+] levels in the fruit fly Drosophila melanogaster. Capa-deficient larvae exhibit low haemolymph Ca[2+] levels, resulting in reduced locomotion and induced elongated pupae that mimic those of animals reared on a Ca[2+]-free diet. Capa secreted from specific neurosecretory cells acts on specialized Ca[2+] storage compartments in the anterior Malpighian tubules, elevating haemolymph Ca[2+]. This endocrine mechanism governing Ca[2+] regulation in terrestrial invertebrates resembles the parathyroid hormone system in vertebrates.